2004
DOI: 10.1002/jgm.481
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo delivery of intact BAC DNA – comparison of different methods

Abstract: These results demonstrate efficient delivery of intact, large (up to 157 kb) DNA constructs for in vitro gene expression and in vivo gene therapy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…More recently, a study carried out with BACs 70-130 kb in size confirmed that Lipofectamine 2000 was the best transfection reagents both in vitro and in vivo, in terms of efficiency and integrity of the transfected DNA. 37 …”
Section: Prospectsmentioning
confidence: 99%
“…More recently, a study carried out with BACs 70-130 kb in size confirmed that Lipofectamine 2000 was the best transfection reagents both in vitro and in vivo, in terms of efficiency and integrity of the transfected DNA. 37 …”
Section: Prospectsmentioning
confidence: 99%
“…17 Nonviral delivery systems based on lipofection, combined or not with polycations, have no size limits and have therefore been used with some success to transfer intact BAC DNA, both in vitro and in vivo. 18 However, this technique requires production and purification of the DNA construct in significant amounts prior to transfection, a step that can in some cases impair its physical intactness.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only few data is available about in vivo electroporation of large DNA molecules. In one study, efficient delivery of an 80-kb BAC into electroporated muscle has been achieved but, as expected, reporter gene expression from the BAC was found 5-fold less efficient than from a plasmid (Magin-Lachmann et al, 2004). Increasing knowledge and technological progress in electroporation has resulted in its clinical application in humans for the treatment of melanoma (Daud et al, 2008) and in several ongoing clinical trials for the treatment of other cancers and for DNA vaccination.…”
Section: Electroporationmentioning
confidence: 84%
“…Initial studies have shown that this results in high levels of gene expression in the liver (Liu, et al, 1999;Zhang et al, 1999). The hydrodynamic injection into the tail vain has also been shown to work relatively well with large BAC DNA (Hibbitt et al, 2007;Magin-Lachmann et al, 2004). Moreover, local hydrodynamic delivery into rabbit liver using catheter-assisted perfusion (Eastman et al, 2002) and pressure-mediated delivery to rat kidney (Maruyama et al, 2002) and to limb muscle of mammals (Hagstrom et al, 2004) have been achieved.…”
Section: Injectionmentioning
confidence: 99%